Owoc granatu. O "Lekcji Tejrezjasza" Janusza Szubera = Pomegranate fruit. About the "Lekcja Tejrezjasza" by Janusz Szuber - Mikołajczak, Małgorzata (1966- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns on the selection of poetry by Janusz Szuber entitled "The Lesson of Tiresias and Other Selected Poems" (2003). The author discusses the main themes and problems raised in this volume and interprets them in relation to the poet`s work and literary tradition.
Keywords: Szuber, Janusz (1947-2020); Lekcja Tejrezjasza; interpretacja; interpretation